Values and the formation of a culture of national defense dental stu-dents - Watanabe-Velásquez, Romel (2016)
Objetive: Determine the influence of values in the formation of a national defense culture in dental students. Materials and method: an explanatory observational, descriptive study, quantitative, cross, consisting of a random sample (simple random selection) of 192 dental students who were studying the semester 2015-2, was distributed by years of studies was conducted first (n = 42), second (n =44), third (n = 33), fourth (n = 39) and fifth (n = 34). The questionnaire reduced Values Scale Schwartz (PVQ-21) for measuring the variable values and questionnaire validated by Suarez, DG and Montano, YM (based on NATID Scale and studies Cesar Cobos Ruiz) version was applied variable measuring the formation of a culture of National Defense. For statistical analysis, the Kolmogorov-Smirnov test was used, Chi square, Spearman coefficient, frequencies and averages. Results: A reliability coefficient of 0.807 for the instrument securities and 0.904 for national defense was found, the variable values presents a predomi-nantly middle and training variable a culture of national defense is high, the chisquare test is significant (50.229) and Spearman Rho is medium (0.546) for the variables under study. Conclusions: There is significant relationship and influence between values and the formation of a culture of national defense.